Analysis of The Relationship Between Financial Distress and Manipulation in Islamic Commercial Banks After COVID-19 - Ichsan Arydani; Sugiyati Fatma Laela (Cakrawala Repositori IMWI, 2024)
This study aims to analyse financial distress and potential financial statement manipulation in Islamic commercial banks. In addition, this study analyses the relationship between the two. Financial distress is measured by the Altman Z-Score m,odelBeneish M-Score measures potential financial statement manipulationh M-Score. The analysis techniques used are descriptive qualitative and Pearson CorrelatioUsinging data from 12 Islamic Commercial Banks in Indonesia for the period 2020 - 2022, the results of the Altman Z-Score calculation show that Islamic commercial banks in Indonesia are financially healthy. This indicates the effectiveness of Islamic bbanks'business strategies, especially in facing the Covid-19 pandemic. The results of the Beneish M-Score calculation prove that Islamic banks are not included in the manipulator category. The Pearson Correlation Coefficient shows that there is no significant relationship between financial distress and financial statement manipulation at Islamic Commercial Banks in Indonesia. The tight supervision by regulators closes the opportunity for manipulation of financial statements. In addition, the characteristics of Islamic banks that are dominated by funds from retail customers can explain the insignificance of the relationship between financial distress and financial statement manipulation.